Sustainable Energy Planning for Nepal in the Federal Structure - Bhusal, Shailendra; Nakarmi, Amrit Man (Journal of Advanced College of Engineering and Management, 2019)
This paper examined the energy planning in each province, sustainable technology policy interventions in the energy demand and social cost benefit analysis in energy sector for Nepal in the federal structure over the period 2017-2050 using LEAP-IBC modeling framework. Four scenarios were developed, reference, Low economy, accelerated economy and sustainable scenario, former three are based on socioeconomic assumption and later is technology intervention case. In reference scenario, energy consumption will increase by 3 folds from 544 PJ to 1645 PJ during 2017-2050, whereas in sustainable scenario the value expected to increase to 866 PJ by 2050. In the base year 2017, emission is 69 million metrictons of Co2 equivalents whereas per capita emission is 2.36 metric tons. In the reference scenario the carbon emission increases to 178 million Metric tons of CO2 equivalent in 2050 whereas per capita carbon emission increases to the 4.06metric ton in the year 2050. In sustainable scenario the carbon emission increases to 21.95 million Metric tons of CO2 equivalent in 2030 whereas per capita carbon emission reduces to the 0.64 metric ton in the year 2030 due to the technological policy intervention. The calculated NPV shows that SED scenario is most economically viable with NPV value 7899 million NRS. In sustainable policy scenario efficient as well as new and improved technologies has been considered as a result of which substantial amount of reduction in energy intensities and per capita final energy consumption is achieved. In reference scenario per capita energy consumption 18GJ is increase to 40 GJ and in sustainable scenario is expected to 19GJ by 2050.